2023
DOI: 10.1002/ps.7354
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation bioaccessibility of inhaled triazole fungicides and health risk assessment during spraying

Abstract: Background: Ambient air pollution caused by pesticide drift has received great attention. To accurately evaluate the health risk of inhaled pesticides, bioaccessibility should be considered. However, methods to reliably assess pesticide residues remain limited, hindering the precise estimation of exposure assessment. We aimed to optimize an in vitro method for the inhalation bioaccessibility (IBA) measurement of triazole fungicides and to incorporate this into inhalation exposure assessment during pesticide sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…These fungicides inhibit the biosynthesis of ergosterol by acting on CYP51 protein. [37][38][39] Because of the high selection pressure of these fungicides, however, resistance has been reported in a variety of pathogenic fungi. [40][41][42][43] Several investigations found that the target gene Cyp51 was upregulated after treatment with triazole fungicides, and overexpression of Cyp51 gene causing triazole fungicide resistance has been reported in a series of plant pathogenic fungi, such as in B. cinerea, Colletotrichum gloeosporioides, and Fusarium fujikuroi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These fungicides inhibit the biosynthesis of ergosterol by acting on CYP51 protein. [37][38][39] Because of the high selection pressure of these fungicides, however, resistance has been reported in a variety of pathogenic fungi. [40][41][42][43] Several investigations found that the target gene Cyp51 was upregulated after treatment with triazole fungicides, and overexpression of Cyp51 gene causing triazole fungicide resistance has been reported in a series of plant pathogenic fungi, such as in B. cinerea, Colletotrichum gloeosporioides, and Fusarium fujikuroi.…”
Section: Discussionmentioning
confidence: 99%
“…Triazole fungicides, as a major class of ergosterol biosynthesis inhibitors, are currently an economically important class of fungicides used in the control of agricultural diseases. These fungicides inhibit the biosynthesis of ergosterol by acting on CYP51 protein 37‐39 . Because of the high selection pressure of these fungicides, however, resistance has been reported in a variety of pathogenic fungi 40‐43 .…”
Section: Discussionmentioning
confidence: 99%